Component Analysis of Volatile Oil from Chrysanthemum morifolium by Supercritical Carbon Dioxide Extraction - Wen, Ming; Jin, Jian-Zhong (Asian Journal of Chemistry, 2014)
In this study, the volatile oil was extracted from Chrysanthemum morifolium by supercritical carbon dioxide extraction. Ninety three peaks were separated and 26 kinds of compounds were identified by GC-MS and their relative contents were determined by area normalization method. The main components in Chrysanthemum morifolium are monoterpenes hydrocarbons, sesquiterpenes hydrocarbons and their oxo-derivatives, etc.